Response of Liquid Organic Fertilizer Application from Sword Fern Weeds and Goat Manure on Growth and Production of Green Beans ( Vigna radiata L ) - Armaniar, Armaniar; Sulardi, Sulardi; Wibowo, Fachrina; Manik, Mika Silviana (Universitas Labuhanbatu, 2023)
The aim of the study was to determine the response of the application of liquid organic fertilizer for weeds of sword ferns and goat manure to the growth and production of green beans (Vigna radiata L). The research method used a factorial Randomized Block Design (RAK) consisting of 2 factors with 16 treatment combinations and 2 replications. The fist factor is treatment of Liquid Organic Fertilizer for sword ferns (M) consisting of 4 levels, namely M0 = 0 cc/L water/plot, M1 = 100 cc/L water/plot M2 = 200 cc/L water / plot, and M3 = 300 cc/ L of water/ plot. The second factor is goat manure ferilizer (S) consisting of 4 levels, namely S0 = 0 kg/plot, S1 = 2 kg/plot, S2 = 4 kg/plot, and S3 = 6 kg/plot. Parameters observed were plant height, number of productive branches, flowering age, plot production, weight of 100 seeds and age of harvest. The results of the study of Liquid Organic Fertilizer treatment of sword fern weeds had an effect on the parameters of plant height, number of productive branches, production per plot, and weight of 100 seeds, but did not affect the parameters of flowering age. The treatment of goat manure had an effect on plant height, number of productive branches, production per plot and weight of 100 seeds, but did not affect the parameters of flowering age. The interaction between the application of Liquid Organic Fertilizer for sword ferns and goat manure did not affect all parameters observed